2010
DOI: 10.1088/0004-637x/710/1/332
|View full text |Cite
|
Sign up to set email alerts
|

A Far-Ultraviolet Survey of M80: X-Ray Source Counterparts, Strange Blue Stragglers, and the Recovery of Nova T Sco

Abstract: Using the ACS on HST, we have surveyed the F UV and NUV populations in the core region of M 80. The CMD reveals large numbers of blue and extreme horizontal branch stars and blue stragglers, as well as ≈ 60 objects lying in the region of the CMD where accreting and detached white dwarf binaries are expected. Overall, the blue straggler stars are the most centrally concentrated population, with their radial distribution suggesting a typical blue straggler mass of about 1.2 M ⊙ . However, counterintuitively, the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 51 publications
0
45
3
Order By: Relevance
“…This is to be expected since it has a U mean magnitude of 19.5 mag. The star V33 was discovered by Dieball et al (2010) in an ultraviolet survey using the Hubble Space Telescope. They reported a UV magnitude for this target of about 19.8 mag.…”
Section: Known Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is to be expected since it has a U mean magnitude of 19.5 mag. The star V33 was discovered by Dieball et al (2010) in an ultraviolet survey using the Hubble Space Telescope. They reported a UV magnitude for this target of about 19.8 mag.…”
Section: Known Variablesmentioning
confidence: 99%
“…Coloured points follow the convention adopted in Table 2 to identify the types of variables found in the field of this globular cluster. Dieball et al (2010) in their ultraviolet survey assigned the label CX01 to an X-ray source that was found to be associated with the position of the Nova at the coordinates RA(J2000) = 16:17:02.817 and Dec(J2000) = −22:58:33.92. These coordinates match with the position of the outburst found in this work and details are given in Table 7.…”
Section: V34: This Is the Nova Discovered By Arthur Von Auwers At Koementioning
confidence: 99%
“…Deep ACS observations of NGC 6397 [411] have identified a substantial population of approximately 150 white dwarfs [453]. Dieball et al [107] have found approximately 30 white dwarfs and about 60 probably cataclysmic variables and white dwarf binaries in M80. In general, however, these searches uncover single white dwarfs.…”
Section: Observationsmentioning
confidence: 99%
“…more massive stars travel towards the cluster centre, but less massive stars, like the HB stars which typically have masses of ≈ 0.5M ⊙ , are pushed out of the dense cluster centre (see e.g. Dieball et al 2010, who derived an average mass of ≈ 0.6M ⊙ for the HB population in M 80).…”
Section: Horizontal Branch Starsmentioning
confidence: 99%